Hutchinson-Gilford progeria syndrome: a rare premature ageing syndrome - Iti Varshney; Mohammad Adil; Syed Suhail Amin; Mohd Mohtashim; Annu Priya; Mahtab Alam (Termedia Publishing House, 2020)
Hutchinson-Gilford progeria syndrome is an extremely rare genetic disorder characterized by premature ageing involving the skin, bones, heart, and blood vessels. The incidence is 1 in several million births. It occurs sporadically and is probably an autosomal dominant syndrome. The diagnosis is essentially clinical and the manifestations become more evident from the first year of life. We report a case of a seven-month- old boy with clinical manifestations characteristic of this syndrome. He had a characteristic "plucked-bird" appearance, prominent eyes and scalp veins, senile look, loss of scalp hair, stunted growth and mottled pigmentation with sclerodermatous changes over the trunk and lower limbs. This interesting case is reported for its rarity.